Numerical simulation of Darcy-Forchheimer flow of Casson ternary hybrid nanofluid with melting phenomena and local thermal non-equilibrium effects - Abbas, Munawar; Khan, Nargis; Hashmi, M. S.; Salleh, Zabidin; Ullah, Hameed; Alsubaie, Abdullah Saad; İnç, Mustafa (Elsevier, 2024)
The Casson fluid flow over a stretching sheet is studied in this work in the presence of porous media with melting heat transfer and chemical reaction, combining nanoparticles of Ti 4 Al 6 V , AA 7072 and AA 7075 with a base fluid of sodium alginate ( NaAlg ). The porous medium Darcy Forchheimer effect is included in the momentum equation. Through the effects of melting, the process of heat transfer is described. In order to explore the features of heat transmission in the absenteeism of LTECs (local thermal equilibrium conditions), the current study employs a mathematical model that has been simplified. For both the solid and liquid phases, the LTNE model yields two different fundamental thermal gradients. This proposed model compares the YOM (Yamada-Ota model) and XM (Xue model), two well-known trihybrid nanofluid models, in terms of performance. After applying the proper transformations, modulated non-linear PDEs (partial differential equations) are simplified in ODEs (ordinary differential equations) and the bvp4c method is used to solve them numerically. A graphic discussion of the relevant factors' significance on the pertinent fields has been presented. It is observed that the Casson ternary hybrid nanofluid temperature and velocity distributions predominate at higher melting parameter. The solid phase's heat transport rate rises with an upsurge in the interphase heat transfer parameter.
Keywords: Casson ternary hybrid nanofluid; Darcy-forchheimer flow; LTNECs (local thermal non-equilibrium condi-tions); Melting phenomena; YOM and XM